CONFLICTS OF MEDIA REPRESENTATION; COMPARING DOMINANT THEORETICAL PERSPECTIVES - Nabeel A; Sundararaman, V (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Society develops through the process of struggles and disputes. The media serves as a platform for staging social conflict and struggle. Therefore, it is important to understand social developments through the many disputes that result in significant protests. Marxian perspective identifies social conflict as interaction with individuals and groups. The technological expansion enabled media to extend the interactions among individuals. Media constitutes ‘struggles over representation’ Shohat and Stam (2014) and ‘conflicts over identity Status’ Rousiley (2014), bringing out social and political issues before the public. These conflicts initiate debate over arguments among audiences. The article reviews various theoretical perspectives on the relationship between representation and identity in social conflict and what is the significance of media representation in the process. The proposed research recognizes a case and employs multiple theoretical perspectives to compare the results. Online news reports (N=100) of the Citizenship Amendment Act (Bill) protests were purposively selected as a case and evaluated using different theoretical frameworks. The researcher questions whether this conflict happened between majority and minority groups and what were the complementing factors for widespread protest across the country. The case study shows critical media literacy is a constructive, essential way with flexible practice in explaining the role of representation and identity in social conflicts for underprivileged groups. The study worries about the implication of critical media literacy as a citizen-centric practice, signifying more exploratory research.